2018
DOI: 10.1145/3272127.3275024
|View full text |Cite
|
Sign up to set email alerts
|

Semantic object reconstruction via casual handheld scanning

Abstract: We introduce a learning-based method to reconstruct objects acquired in a casual handheld scanning setting with a depth camera. Our method is based on two core components. First, a deep network that provides a semantic segmentation and labeling of the frames of an input RGBD sequence. Second, an alignment and reconstruction method that employs the semantic labeling to reconstruct the acquired object from the frames. We demonstrate that the use of a semantic labeling improves the reconstructions of the objects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…SSCNet [SYZ*17] uses a dilation‐based 3D context module to efficiently expand the receptive field and enable 3D context learning. Hu et al [HWVK*18] design a deep network to produce semantic labels of the RGBD frames, and then use these labels to improve the quality of semantic reconstruction. Hou et al [HDN19] present 3D‐SIS network, which takes the 2D/3D features into training and achieves instance segmentation result from the entire 3D scene.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…SSCNet [SYZ*17] uses a dilation‐based 3D context module to efficiently expand the receptive field and enable 3D context learning. Hu et al [HWVK*18] design a deep network to produce semantic labels of the RGBD frames, and then use these labels to improve the quality of semantic reconstruction. Hou et al [HDN19] present 3D‐SIS network, which takes the 2D/3D features into training and achieves instance segmentation result from the entire 3D scene.…”
Section: Related Workmentioning
confidence: 99%
“…According to the data processing type, state‐of‐the‐art (SOTA) methods of 3D semantic reconstruction can be roughly divided into two main classes. One class of methods ( e.g ., [KMYG12], [CLW*14], [HZCP16], [HWVK*18], [HSXF19]) rely on the geometry post‐processing techniques: they stop the sensor scanning, then segment the whole reconstructed 3D scene model into individual objects. Another class of methods (e.g., [TTN16], [RA17], [MHDL17], [RBA18], [LZZZ18]) adopt online processing pipeline, which directly project 2D segmentation results to 3D space, yielding individual reconstructed 3D models.…”
Section: Introductionmentioning
confidence: 99%
“…None of the previous approaches for scan automation was designed to utilize geometric priors of mechanical parts or CAD models; they assume a continuous [5], [6] smooth surface [4], [7]. Hu et al [33] suggested a method to incorporate semantic labeling instead of primitive labels, to assist registration and reconstruction during the scanning stage. However, in contrast to our work, this work is focused on registration and reconstruction, and the problem of exhaustive scan path is still in the control of the user without any systematic suggestions.…”
Section: B Scan Path Generationmentioning
confidence: 99%